Avaliação de polimorfismos nos genes GSTM1 e GSTT1 e a associação com endometriose em mulheres de Mato Grosso – Brasil - Kubiszeski, Eloísa Helena (2013)
Endometriosis is a common gynecological disease, characterized by growth and implantation of endometrial tissue outside the uterine cavity. Its etiology is complex and immune factors, hormonal and genetic factors have been proposed to explain the susceptibility to disease. Polymorphisms in genes involved in detoxification of xenobiotics and metabolism of sex steroids have been described, among them the genes of the Mu class of the glutathione Stransferase (GSTM1) and theta gene system glutathione transferase (GSTT1). The presence of these polymorphisms results in the lack of activity of these enzymes and a greater risk of developing endometriosis in women. Objective: This study tevecomo objectives: to estimate the frequencies of polymorphisms in GSTM1 and GSTT1 genes in women with and without endometriosis and verify possible association with these polymorphisms. Material and Methods: We conducted an observational epidemiological case-control, and the sample was composed of 218 women (121 casos/97 controls). The presence or absence of endometriosis was confirmed by the visualization of lesions by laparoscopy and histopathology. The extraction of DNA from peripheral blood sample was performed using the technique of salting out and multiplex PCR for identification of polymorphisms in GSTM1 and GSTT1. Results: It was observed frequency of GSTM1 polymorphism in the gene identified in women with and without endometriosis were 54.50 and 51.50% respectively. For GSTT1, the frequencies corresponded to 20.70% in cases and 33% in controls (p = 0.0395). There were no differences in the frequencies of GSTM1 gene polymorphisms in cases and controls (p = 0.659). Thus, GSTM1 polymorphism did not confer susceptibility to endometriosis. However, the GSTT1 gene polymorphism was associated women with conferring protection. We supposed that the presence of the polymorphism in GSTT1, the absence of this gene activity may contribute to the increased production of reactive oxygen species, which in turn may promote DNA damage and consequently apoptosis. Thus, such effects in healthy women not contribute to the implantation of endometrial tissue. In addition to this assumption, the contribution of the products of other polymorphisms in genes involved in the synthesis and metabolism of steroids, plus others not yet known, should be considered and investigated in future researches.